Comparison of Nurcholis Madjid and A. Hasyim Muzadi's Thoughts on Renewal in Indonesia - Aam Saepul Alam; Rafiudin Rafiudin; Adang Sonjaya (International Journal of Islamic Khazanah, 2020)
This study aims to understand the differences and similarities in the thinking of two figures from different organizations. Two different thinkers and reformers of educational and organizational genealogy, namely Nurcholis Madjid and Hasyim Muzadi. Nurcholis Madjid (Cak Nur) graduated from Western education, and Hasyim Muzadi graduated from a local boarding school education. The method used in this study, using a qualitative approach with a Comprehensive Study approach and through the Hermeneutic approach. Observing the results of the study provides insight into Nurcholis Madjid and A. Hasyim Muzadi, having differences in their ideas. Nurcholis Madjid gave birth to Universal Islamic ideas, and Hasyim Muzadi gave birth to rahmatan lil alamin in religious contexts. The similarity of the two figures is to promote Islam that is full of peace, harmony, and harmony.